Postoperative Ileus with the Topical Application of Tongfu Decoction Based on Network Pharmacology and Experimental Validation. (28th March 2022) - Zuo, Ximeng; Shi, Xiaoguang; Zhang, Xuedan; Chen, Zhenzhou; Yang, Zhenrui; Pan, Xiaojuan; Lai, Rui; Zhao, Ze
Abstract : Objective . Postoperative gastrointestinal dysfunction is a common and important complication of surgery. This study aimed to explore the key pharmacological mechanisms of Tongfu decoction in treating postoperative ileus (POI). Methods . The active ingredients of Tongfu decoction and their targets were screened using the TCMSP database and STITCH and SwissTargetPrediction databases, respectively. The GeneCards and DisGeNET databases were used to obtain POI dysfunction-related therapeutic targets. After screening, a drug-active-ingredient-therapeutic target network was constructed and the key target functional enrichment analysis was carried out. The Sprague–Dawley rats with POI were used for in vivo experimental verification. The serum levels of IL-1 β, IL-6, IL-10, IFN- γ, and MCP-1 were measured after surgery using enzyme-linked immunosorbent assay. The Western blot analysis was used to determine the expression of key proteins of the PI3K-Akt signaling pathway in colon tissues. Results . An interaction network was constructed containing 7 Chinese medicine components, 36 compounds, and 85 target proteins. The functional enrichment analysis showed that the target proteins mainly acted on the POI through the PI3K-Akt signaling pathway. In in vivo experiments, Tongfu decoction had a promoting effect on the serum level of IL-10, an inhibitory effect on the serum levels of IL-1 β and CCL2, and an inhibitory effect on the local expression of PI3K, pAkt, and mTOR in colon tissue. In addition, the Tongfu decoction increased the intestinal ink advancing rate. Conclusion . Nonoral Tongfu decoction can also be used to treat POI; its mechanism is affected by IL-10 and IL-1 β .The inhibition of the PI3K-Akt signaling pathway affected the treatment with Tongfu decoction by inducing an immune-inflammatory storm in POI.